Tindak Pidana Penyerobotan Tanah - Marjan, Muh Efendi; Toule, Elsa Rina Maya; Latupeirissa, Julianus Edwin (Bacarita Law Journal, 2023)
This study aims to find out: what are the material elements of land grabbing that can be punished, and what are the judges'juridical considerations of criminal acts of land grabbing. Normative Juridical Research Research. Legal research is conducted to find solutions to legal issues that arise, primary data and secondary data are analyzed descriptively. This research is directed to be able to study and analyze whether land grabbing can be criminalized or not, analyze and explain the application of criminal law to criminal acts of land grabbing. The results showed that the judge who examined and tried the case with register number 225/Pid.B/2015/PN.Kla stated that the defendant was proven to have committed the act as charged by the first and second charges, but the panel of judges decided to release the defendant from all charges. law because the actions committed by the defendant are not a crime (onslag van recht vervolging). The Judge considered that the indictment submitted by the Public Prosecutor at the trial was in accordance with the actions of the defendant, but based on the results of the trial facts the Panel of Judges who examined and tried the case with register number 225/Pid.B/2015/PN.Kla did not find any action crime from the defendant's actions during the evidentiary process.